Invasive Fungal Infections (IFI) After Heart Transplantation (HT): An 11-Year, Single-Center Experience. (4th October 2017) - Lin, Michael; Echenique, Ignacio; Angarone, Michael; Anderson, Allen; Stosor, Valentina
Abstract: Background: Invasive fungal infections disproportionately affect organ transplant recipients, causing significant morbidity and mortality. The cumulative incidence of IFIs following HT varies by era, center, and immunosuppression practices, ranging from 4% to >25%. Methods: We conducted a prospective observational cohort study of HT recipients from June 2005 to June 2016 to define the contemporary incidence, epidemiology, and outcomes of IFI after HT. Probable and proven IFIs were defined by EORTC/MSG criteria. Results: In total, 256 HT recipients were followed for mean 1, 184 days (0–3, 076 days). 140 (55%) and 61 (24%) received basiliximab and thymoglobulin (ATG) induction, respectively, followed by tacrolimus, mycophenolate, and prednisone. 238 (93%) received ≥3 months of prophylaxis with clotrimazole and 24 (9%) received antifungal prophylaxis with voriconazole. Twenty-three IFIs occurred in 23 patients (9%) at mean of 283 day post-HT (range 2–1, 579 days), with one pulmonary C ryptococcus, seven invasive Candida (five with candidemia), seven pulmonary Aspergillus, three pulmonary Rhizopus, two Histoplasma, two Blastomyces, and one multifocal cutaneous Alternaria . Univariate predictors of IFI were Hispanic ethnicity (17.4% vs. 5.6%, P = 0.05), ATG induction (43.5% vs. 21.9%, P = 0.02), diabetes mellitus (DM) (52.2% vs. 27.0%, P = 0.01), re-operation (39.1% vs. 20.6%, P = 0.04), and heart–kidney transplant (17.4% vs. 5.2%, P = 0.04), but not age (57 vs. 56.6, P = 0.92), male gender (69.6% vs. 68.7%, P = 0.93), Caucasian race (69.6% vs. 67.8%, P = 0.86), chronic kidney disease (30.4% vs. 40.8%, P = 0.33), lower nadir absolute neutrophil count (1, 909 vs. 2280 cells/μL, P = 0.33), re-transplantation (4.3% vs. 3.4%, P = 0.58), any rejection (43.5% vs. 36.5%, P = 0.51), or CMV infection (8.7% v. 14.2%, P = 0.75). Recipients with IFI had higher overall (43.5% vs. 18.5%, P = 0.01) and 1-YR (30.4% vs. 7.3%, P = 0.002) mortality, with attributable mortality 17.4%. Conclusion: IFI occurred in 9% of HT recipients at our center and were associated with high mortality. Important potential predictors of IFI were ATG induction, DM, re-operation and heart-kidney transplant. These factors represent potential identifiers for targeted antifungal prophylaxis and risk reduction strategies. Ethnic disparities in development of IFI require further investigation and validation. Disclosures: All authors: No reported disclosures.